Patient experiences with liraglutide for obesity and binge eating disorder–A qualitative study - Ingrid Sørdal Følling; Stine Larsen Reigstad; Åsne Ask Hyldmo; Anne-Sofie Helvik (PLoS ONE, 2025)
Introduction Obesity is a growing health concern and a known risk factor for binge eating disorder (BED). BED is characterized by episodes of overeating with a loss of control, often leading to psychological distress. In some cases, medication may be recommended to manage depressive symptoms and support weight loss. Liraglutide, a glucagon-like peptide-1 (GLP-1) analog, works by targeting the brain’s reward system to reduce psychological stress and enhance feelings of fullness. However, there is limited research on the use of liraglutide for patients with both obesity and BED. This qualitative study aimed to investigate how patients with these conditions experience treatment with liraglutide. Methods A qualitative design with individual semi-structured, in-depth interviews was employed. Eight informants aged 25–60 years were interviewed, and data were analyzed using systematic text condensation. Results Two main themes, each with three associated subthemes, emerged. The first main theme was: The role of food on the expression of BED , with subthemes: Food as an emotion regulator, Persistent thoughts on eating and dieting , and Emotional and situational triggers for binge eating . The second main theme was Experiences with liraglutide in managing BED , with subthemes: Meeting emotional and physical needs, Reducing thoughts about food , and Decreasing triggers for eating . The experiences with medication (main theme 2) influenced the expression of BED (main theme 1) as informants reported that liraglutide impacted their BED symptoms. Discussion Findings suggest that patients with obesity and BED found liraglutide helpful in addressing emotional and physical needs, enhancing emotional well-being, social interactions, and overall quality of life. Further qualitative research is needed to explore the long-term impact of liraglutide on emotional and behavioral changes in this population.